Checklist of decapod crustaceans from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: IV. Infraorder Anomura: Superfamilies Chirostyloidea, Galatheoidea, Hippoidea and Paguroidea - Mantelatto, Fernando L.; Miranda, Ivana; Vera-Silva, Ana L.; Negri, Mariana; Buranelli, Raquel C.; Terossi, Mariana; Magalhães, Tatiana; Costa, Rogério C.; Zara, Fernando J.; Castilho, Antonio L. (Zootaxa, 2021)
This checklist is the fourth contribution resulting from a long-term multidisciplinary project which combined morphological analyses and molecular techniques (mitochondrial DNA markers) for accurate identification of marine and coastal decapod crustaceans of São Paulo State (Brazil). We provide a list of 63 species of the following 11 families of 4 superfamilies of Anomura: Albuneidae (4 spp.), Blepharipodidae (1 sp.), Chirostylidae (1 sp.), Diogenidae (18 spp.), Hippidae (1 sp.),  Munididae (8 spp.), Munidopsidae (1 sp.), Paguridae (13 spp.), Parapaguridae (2 spp.), Porcellanidae (13 spp.), and Pylochelidae (1 sp.). Seven species previously reported from the region were neither collected nor found in museum collections during our study, including one (Sympagurus dimorphus) that we suggest to be removed from São Paulo coast fauna lists. We generated new sequences of cytochrome oxidase subunit I (barcode region) and 16S genes of 44 species. This anomuran inventory may serve as guideline for future studies on taxonomy, conservation, population genetics, biogeography, and phylogenetics, which might flag species that deserve further investigations and concerns.